Constructing and Deconstructing the Home Front: The Badger Army Ammunition Plant and Rural Wisconsin, 1941-1998 - Baum, Emily (My University, 2017)
The Badger Ordnance Works was once the largest ammunition plant in the world, producing thousands of tons of propellants, explosives, and acids over the course of three wars. By March of 1942, the farmers who had fought to keep their land had moved away and construction on the Plant had begun; a village was erected for workers to live in if they were not from a nearby area. At the end of World War II, the B.O.W. closed, only to reopen under new ownership to produce materials for the Korean War. After being shut down after the Korean War, the newly named Badger Army Ammunition Plant would be reactivated to produce ammunition for the Vietnam War, and would close down again when the war ended. While rumors would swirl that the Plant would be opened yet again, in 1998 the Army officially declared that the Badger Army Ammunition Plant would never again open its doors. This began a new phase in the life of the B.A.A.P., which would focus on decontaminating the location before tearing it down, and the finalization of what will happen with the land the Plant stood on. This paper will examine the controversy surrounding the construction of the Plant before looking at the lives of individuals working at the Plant during the Second World War, the Korean War and the Vietnam War. Finally, the paper will close by exploring the reactions to the closing of the Plant and the hopes for the future of the site. Throughout all of this, the concepts of home front and community will be examined as both were essential components of the Plant, as well as its significant role in the history of one region in Wisconsin. This will be explored through a variety of primary and secondary sources, ranging from stories from people who worked at the Plant to visiting the Museum that stands on the land that once held a Plant that was one dubbed the largest ammunition Plant in the world.
Keywords: Weapons industry--Employees; Ammunition--Wisconsin; Badger Army Ammunition Plant (Baraboo, Wis.); Badger Ordnance Works (Wis.)